Esensi Alam Semesta Beserta Tujuannya dalam Perspektif Filsafat Pendidikan Islam - Khairani, Aulia; Rahman, Aulia; Hasanah, Nur Arifa; Paramitra, Tiara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Nature is an omnipotent form created by God. Looking for extraordinary creations shows how beautiful nature is created. Of course, with all kinds of objects that show every beauty, this is the masterpiece of Allah SWT. The essence of the universe is what it is though, God's intention to create the universe for us, how good nature is for us, the universe for us and others. Regarding God's purpose in creating the universe, basically it is a means of conveying information to people and proof of the existence and omnipotence of Allah SWT, that there is an Almighty God who controls this world and creates something that is without error. For example, night cannot precede day, planets rotate along circular paths until the arrival of the final judgment etc. Basically, nature is none other than Allah swt. That's why the spectrum of nature is very large. The universe was created to store so many secrets, since the extraordinary process of its formation is very complex and its inhabitants are diverse, it is an interesting study. Nature has the same basic word as the address, which means something if we follow it, we arrive at the intended destination. That is, if we take a serious study of nature, it will lead us there, its creator is Allah SWT. Nature is also related to the word science, this shows that the essence of the universe is full of scientific mysteries. Let's look at the philosophy of Islamic education, in essence this universe is not just a place to live, but the universe is actually a place of learning for the community. Keywords : Universe, Goal